2018
DOI: 10.1109/tnsre.2018.2877962
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Semi-Active Variable Stiffness Foot Prosthesis

Abstract: This paper presents the design and validation of a novel lower-limb prosthesis called the Variable-Stiffness Foot (VSF), designed to vary its forefoot stiffness in response to user activity. The VSF is designed as a semi-active device that adjusts its stiffness once per stride during swing phases, in order to minimize size, mass and power consumption. The forefoot keel is designed as an overhung composite beam, whose stiffness is varied by moving a support fulcrum to change the length of the overhang. Stiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Stiffness change of 51% was demonstrated. Although the change achieved is less than demonstrated in previous work [11,12] it is considerably higher than the reported user perception of 8% [13]. Furthermore, for the given system and boundary conditions, it was presented that the dissipation of a damping element will reach a maximum at a given value of damping coefficient.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Stiffness change of 51% was demonstrated. Although the change achieved is less than demonstrated in previous work [11,12] it is considerably higher than the reported user perception of 8% [13]. Furthermore, for the given system and boundary conditions, it was presented that the dissipation of a damping element will reach a maximum at a given value of damping coefficient.…”
Section: Discussionmentioning
confidence: 54%
“…Recent publications demonstrate an increased research interest in prosthetic feet that have adjustable stiffness and the effect of prosthetic stiffness on user in different tasks. Prosthetic feet with modular ankle stiffness have been proposed by Shepard et al [11] and Glanzer et al [12]. These devices alter stiffness by shifting a support in a beam deflection system, allowing a change in forefoot stiffness between steps.…”
Section: Introductionmentioning
confidence: 99%
“…As our study, and other studies have found [57, 58, 61], the biological limbs have an inherent ability to modulate joint/limb stiffness based on the demands of locomotion. As such, a device that incorporates micro-motors to alter the stiffness characteristics [70, 71] may be a viable solution to replicate salient features of the biological foot and ankle system.…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide the adaptability offered by powered prostheses in a potentially smaller, lighter, and quieter package, computer-controlled, primarily passive devices have recently been developed in both the academic and industrial settings [28][29][30][31][32][33]. These primarily passive devices rely on energetically passive mechanisms such as springs and dampers during the load-bearing phases of gait with low-power actuators to modulate the passive parameters of these elements.…”
Section: Introductionmentioning
confidence: 99%